Analytical evaluation and critical appraisal of early commercial SARS-CoV-2 immunoassays for routine use in a diagnostic laboratory. Issue 3 (3rd July 2021) - Cramer, A; Goodman, N; Cross, T; Gant, V; Dziadzio, M
ABSTRACT: Background : The objective of this study was to evaluate the performance characteristics of early commercial SARS-CoV-2 antibody assays in mild and asymptomatic subjects to enable the selection of suitable immunoassays for routine diagnostic use. Methods : We used serum samples from a pre-COVID era patient cohort (n = 50, pre-December 2019), designated SARS-CoV-2 negative, and serum samples from a SARS-CoV-2 RT-PCR-positive cohort (n = 90) taken > 14 days post-symptom onset (April–May 2020). Six ELISA assays were evaluated, including one confirmation assay to investigate antibody specificity. We also evaluated one point-of-care lateral flow device (LFIA) and one high throughput electrochemiluminescence immunoassay (CLIA). Results : The ELISA specificities ranged from 84% to 100%, with sensitivities ranging from 75.3% to 90.0%. The LFIA showed 100% specificity and 80% sensitivity using smaller sample numbers. The Roche CLIA immunoassay showed 100% specificity and 90.7% sensitivity. When used in conjunction, the Euroimmun nucleocapsid (NC) and spike-1 (S1) IgG ELISA assays had a sensitivity of 95.6%. The confirmation Dia.Pro IgG assay showed 92.6% of samples tested contained both NC and S1 antibodies, 32.7% had NC, S1 and S2 and 0% had either S1 or S2 only. Conclusions : The Roche assay and the Euroimmun NC and S1 assays had the best sensitivity overall. Combining the assays detecting NC and S1/S2 antibody increased diagnostic yield. These first-generation assays were not calibrated against reference material and the results were reported qualitatively. A portfolio of next-generation SARS-CoV-2 immunoassays will be necessary to investigate herd and vaccine-induced immunity.